Pengaruh Pemberian Tepung Jerami Bawang Merah (Allium ascalonicum L ) Terfermentasi Dalam Ransum Terhadap Recahan Karkas Ayam Kampung Super Umur 10 Minggu - Noviana Pedi Bili; Ni Ketut Etty Suwitari; Ni Made Yudiastari (GEMA AGRO, 2026)
Empowerment of local chickens in Indonesia continues to be developed by various parties, both government and private, considering the high demand for meat and eggs, animal protein needs can be met through super native chickens. The purpose of this study is to determine the effect of providing fermented shallot straw flour in rations on carcass fragments of 10-week-old super native chickens and to find out what percentage level of fermented shallot straw flour in rations is able to provide the best results on carcass fragments of 10-week-old super native chickens. The current reality is that the price of commercial feed on the market is felt by farmers to be very expensive, while feed is the largest component in the poultry farming business, where feed costs can reach 60-70% of total production costs, so it is very important to find other alternative feeds in the availability of ration feed ingredients to reduce production costs as small as possible without reducing optimum production. Utilizing feed ingredients that are easily available and reduce the cost of purchasing feed ingredients, without affecting the productivity of super native chickens. Therefore, the method that can be done is to utilize alternative feed ingredients, namely shallot straw which is widely available and easily obtained. Research Design: The design used in this study was a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications. P0 = Control ration without the addition of fermented shallot straw meal. P1 = Ration containing 3% fermented shallot straw. P2 = Ration containing 6% fermented shallot straw. P3 = Ration containing 9% fermented shallot straw. P4 = Ration containing 12% fermented shallot straw. Based on the results of the study, the administration of fermented shallot straw meal in the super kampung chicken ration had no significant effect (P>0.05) on all observed variables (breast weight, thigh weight, back weight, and wing weight). The administration of fermented shallot straw meal at a level of 3% in the ration showed the best results for carcass breakdown of super kampung chicken.   Keywords: Super Village Chicken, Carcass Breakdown, Fermented Shallot Straw Meal